Export Complexity and Economic Growth: Empirical Analysis for Selected CEE Countries - Darko Lazarov; Goce Petreski (Croatian Economic Survey, 2023)
The principal objective of the paper is to test the hypothesis that export sophistication (complexity) rather than the volume of exports has a more robust impact on economic growth. We applied a dynamic panel specification model (system GMM) to a sample of 22 selected CEE countries in the 2009–2019 period. Estimated research results suggest that export still plays a significant role in determining economic growth in these countries. However, the analysis shows that export sophistication (complexity) has a predominant role in stimulating economic growth for the observed sample of countries. In addition to the main focus of the paper, estimated results show that FDI inflows have a positive and statistically significant direct and indirect impact on economic growth. Moreover, the results indicate that, apart from the direct effects of export sophistication on economic growth, it has an additional positive effect on export performance through structural transformation. When comparing the impact of export sophistication on economic growth, the difference between EU and non-EU economies seems to be mostly insignificant.